THU0254 TRENDS OF SEVERITY, PROGRESSION AND BURDEN OF DISEASE IN THE "ATTIKON" SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) COHORT: EVIDENCE FOR THE RULE OF "ONE THIRD" IN DISEASE SEVERITY. (June 2019) - Nikolopoulos, Dionisis; Pieta, Antigoni; Kostopoulou, Myrto; Erden, Abdulsamet; Katsimbri, Pelagia; Boumpas, Dimitrios; Fanouriakis, Antonis
Abstract : Background: SLE phenotype, severity and prognosis varies widely, while its course, prognosis and pattern of severity cannot be predicted with confidence. Objectives: We analyzed the phenotype and severity patterns of a SLE cohort in the Attica area of Greece, based in "Attikon" University Hospital, and assessed whether these patterns change over the course of the disease. Methods: Retrospective cohort study of 512 Caucasian SLE patients fulfilling the ACR 1997 and/or SLICC 2012 criteria. Data on clinical course, pattern of severity and SLICC damage index (SDI) were recorded for each patient at the time of diagnosis and at last evaluation. Severity of disease was stratified based on BILAG manifestations and patients were assessed for progression to a more severe phenotype over their disease course. Patients with disease duration < 12 months were excluded. Binary logistic regression was performed to identify independent predictors of such progression. Results: More than half patients (53.7%, 275/512) presented with mild disease, while in approximately 20% (20.8%, n=106) lupus presented with severe manifestations at diagnosis. Median (IQR) follow-up was 96.5 (144) months. Of 246 patients with initially mild disease, 126 (56.4%) retained their mild phenotype, 73 (29.7%) progressed to a moderate phenotype, while the remaining 47 (19.1%) eventually developed severe lupus. Also, 30 patients (29.4%, 30/102) who initially manifested moderately severe manifestations progressed to severe disease over time. At last evaluation, a nearly equal distribution in severity patterns was evident (mild 30%, moderate 34% and severe 36%). Independent factors for disease progression were older age at diagnosis (OR: 0.97 per 1-year, 95% CI 0.95-0.98), disease duration (OR: 1.10 per 1-year, 95% CI 1.06-1.13), positive anti-dsDNA (OR: 2.20, 95% CI 1.38-3.49) and presence of fever at diagnosis (OR: 1.67, 95% CI 1.00-2.77). By multivariate regression, only disease duration (OR: 1.09, 95% CI 1.05-1.12) and anti-dsDNA (OR: 1.73, 95% CI 1.05-2.85) were independently associated with disease progression. Ninety-two subjects (18%) had organ damage at the time of diagnosis, mainly due to neuropsychiatric and thrombotic events. At last visit, mean (SE) SDI was 0.67 (0.57). Two-hundred eight patients (59.8%) had no damage (SDI=0), while high damage (SDI ≥ 3) was measured in 25 subjects (7.2%). Conclusion: In this SLE cohort of Caucasian patients, almost half of cases have mild disease at presentation, yet with significant damage accrual. Of patients with disease duration ≥1 year, 43.1% progressed to more severe phenotypes, with patients distributed evenly in the mild, moderate and severe categories. These data reiterate the rule of one third for severity observed in other autoimmune diseases. Disclosure of Interests: Dionisis Nikolopoulos: None declared, Antigoni Pieta: None declared, Myrto Kostopoulou: None declared, Abdulsamet Erden: None declared, Pelagia Katsimbri: None declared, Dimitrios Boumpas: None declared, Antonis Fanouriakis Paid instructor for: Amgen, GSK, Speakers bureau: Abbvie, Enorasis, Genesis Pharma